2017
DOI: 10.1590/0100-29452017097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thidiazuron Concentration and Application Period on ‘Royal Gala’ Apple Fruiting and Production

Abstract: -'Gala' apple trees have low fruit set in restrictive pollination situations, being an obstacle to the achievement of high production rates in orchards in southern Brazil, which can be minimized by the use of growth regulators. The aim of this study was to evaluate the effect of thidiazuron concentrations in 'Royal Gala' apple fruiting and production, grown in mild winter conditions. The experiment was conducted during the 2011/2012, 2012/2013 and 2013/2014 crop years in Fraiburgo, SC, on 'Royal Gala' apple t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The use of TDZ without pollinator visits resulted in absence of seeds (Table 3). Fagundes et al (2017) found a small number of seeds in fruits produced with the use of TDZ, with 3.8 to 4.1 for the control and 2.3 to 2.4 for TDZ applications.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The use of TDZ without pollinator visits resulted in absence of seeds (Table 3). Fagundes et al (2017) found a small number of seeds in fruits produced with the use of TDZ, with 3.8 to 4.1 for the control and 2.3 to 2.4 for TDZ applications.…”
Section: Resultsmentioning
confidence: 93%
“…The treatment with only TDZ application resulted in significantly lower fruit weight than those with floral visitors in the 2017/2018 growing season (Table 4). The lower fruit weight found in the treatment with only TDZ application may be connected to the higher number of set fruits, which can lead to increased competition for photoassimilates (Fagundes et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…26 It is also used in plant in vitro cultures to improve yields per plant. For example, Fagundes et al 27 obtained a higher yield of fruits per plant and effective fruit mass by the use of TDZ. Its morpho-regulatory potential has led to its application in plant tissue culture for morphogenic system development.…”
Section: Applications Of Thidiazuron In Plant Tissue Culturementioning
confidence: 99%
“…It is also used in plant in vitro cultures to improve yields per plant. For example, Fagundes et al 27 . obtained a higher yield of fruits per plant and effective fruit mass by the use of TDZ.…”
Section: Applications Of Thidiazuron In Plant Tissue Culturementioning
confidence: 99%
“…The quality of flower buds and the environmental conditions before, during and after flowering are also extremely important factors. Fruit set can be severely impaired by insufficient chilling during the winter, resulting in the asynchrony of the flowering period between cultivars [1], by rains and frosts during the flowering period. Consequently, the grower needs to explore all the possibilities that can contribute to a good fruit set, especially in years of adverse pollination conditions or with low flowering intensity [2].…”
Section: Introductionmentioning
confidence: 99%